Уточнена модель структурних перетворень в тонкому сталевому циліндрі при тепловому опроміненні торця - Жук, Я.О.; Червінко, О.П.; Васильєва, Л.Я. (Видавничий дім "Академперіодика" НАН України, 2007)
Phase transformations in a steel thin cylinder under thermal pulse irradiation of the cylinder end are studied. The statement of a dynamic problem of coupled thermomechanics along with a thermodynamically consistent theory of the inelastic behavior of a material is used. The model is refined to take account for temperature-induced phase transformations. The residual stress-strain and structural states of the steel cylinder are studied by the numerical simulation.